Mengembangkan Nilai Agama Dan Moral melalui Pendampingan Manasik Haji Di Tk Islam Saadatutddarain - Azhari, Supian; Zain Rahmatul Aini; Yuliana; Maesarah (Jurnal Pendidikan Islam Anak Usia Dini Al-Amin, 2023)
This research is motivated by the learning process related to the implementation of the Hajj manasik carried out by early childhood education institutions at Tk Islam Saadatutddarain the aim is to develop religious and moral values towards children. The development of religious and moral values is to provide a basic foundation for children in building akhlakul karimah, courtesy, always obeying the rules of Allah and staying away from all prohibitions and being able to tolerate each other. The method used in this research is to use descriptive qualitative methods and the object of this research is the teacher and children in the Saadatutddarain Islamic Kindergarten educational institution in Central Lombok. The results of this study are the efforts made in developing religious and moral values through the Hajj manasik can be carried out in accordance with the planning and implementation runs smoothly and conducive. The method used in the implementation of this activity is by practicing directly with children in the school yard and this method really helps the teacher in its implementation. The impact of this implementation is that children are enthusiastic and help each other in carrying out Hajj rituals and can get a very extraordinary fun experience with their friends.